Chlorogenic acid improves diabetic retinopathy by alleviating blood‐retinal‐barrier dysfunction via inducing Nrf2 activation. (8th February 2022) - Ouyang, Hao; Du, Ao; Zhou, Lingyu; Zhang, Tianyu; Lu, Bin; Wang, Zhengtao; Ji, Lili
Abstract: As one of the major diabetic microvascular complications, diabetic retinopathy (DR) is mainly initiated by the blood‐retinal barrier (BRB) dysfunction. Chlorogenic acid (CGA) is a natural polyphenolic compound in Lonicerae Japonicae Flos, which traditionally has the beneficial function for eyes and is commonly included in many anti‐diabetic formulas. In this study, the potential protective mechanism of CGA against DR was investigated. Streptozotocin (STZ) was used to induce diabetes in mice. CGA attenuated BRB dysfunction and reversed endothelial‐mesenchymal transition (EndoMT) and epithelial‐mesenchymal transition (EMT) in retinas in vivo . CGA inhibited microglia activation and reduced tumor necrosis factor (TNF)α release both in vivo and in vitro . CGA promoted nuclear factor erythroid 2‐related factor 2 (Nrf2) activation and prevented EndoMT/EMT in TNFα‐treated human retinal endothelial cells (HRECs) or retinal pigment epithelial APRE19 cells. CGA alleviated endothelial/epithelial barrier oxidative injury in HRECs or APRE19 cells stimulated with TNFα, but this effect was disappeared in cells co‐incubated with Nrf2 inhibitor. Additionally, the CGA‐supplied alleviation on BRB damage and EndoMT/EMT was markedly weakened in retinas from STZ‐treated Nrf2 knock‐out mice. All results suggest that CGA improves DR through attenuating BRB injury by reducing microglia‐initiated inflammation and preventing TNFα‐induced EndoMT/EMT and oxidative injury via inducing Nrf2 activation.